Strengthening Youth Morality through Faith, Technology, and Community Empowerment; A Sustainable Education Model In Aceh. - Hayati; Aisyah; Sri Hardianty (JKA, 2025)
The moral decline among Indonesian youth, especially in Aceh, requires serious attention in the context of rapid globalization and digitalization. This study aims to formulate a sustainable education model that combines faith, technology, and community empowerment to strengthen the moral character of the younger generation. The method used is a qualitative study with a case study approach in several Acehnese youth communities. Data were obtained through in-depth interviews, field observations, and documentation. The results of the study indicate that strengthening spiritual values through faith-based education, creative and positive use of technology, and active involvement in social activities can increase moral awareness and social responsibility of youth. These findings underline the importance of collaboration between educational institutions, religious leaders, and the community in building a sustainable contextual education model. This model is proposed as an alternative strategy in responding to moral resistance in the digital era.